Effect on rat blood pressure of epitaondiol, diterpenoid isolated from the Algae Stypopodium flabelliforme of Rapa NIU (Chilean Island Territory in the Pacific Ocean) - Martinez, J.L.; Vinet, R.; Laurido, C.; Jaimes, L.; Vargas-Rueda, S.; Rovirosa, J.; San Martin Barrientos, Aurelio Del Carmen (My University, 2016)
Easter Island is an island territory of Chile located in the middle of the Pacific Ocean. It is characterized by a great maritime wealth and endemism. We worked with a epitaondiol compound, isolated from the alga Stypopodium flabelliforme, which is also producer of a number of secondary metabolites. In this article, the effect of mono- and di epitaondiol acetate was studied on blood pressure in normotensive rats. The results are important but do not show significant difference as antihypertensive, but the recovery period is prolonged. These results prove to be pioneers in the study on blood pressure of chemical compounds isolated from Easter Island algae.
Keywords: chile; easter island; epitaondiol; mean arterial pressure; stypopodium flabelliforme